Effects of task complexity on narrative writing performance among ESL learners - Ismail, Lilliati (Medwell Publications, 2019)
There has been burgeoning interest in investigating the effects of cognitive load on task performance among second and Foreign language learners in the past few decades. Two cognition constructs that have dominated the discussion on the effects of cognitive complexity on language performance are Robinson’s cognition hypothesis and Skehan’s trade-off hypothesis. While Robinson argued that increasing task complexity levels would result in heightened attention to accuracy and complexity, Skehan posited that more demanding tasks would result in a depletion of attention for certain aspects of language production. The current study investigated the effects of high and low complexity tasks in terms of here-and-now versus there and-then, under pre-task and no pre-task planning conditions on narrative writing performance. The participants were 65 English as a Second Language (ESL) learners. The t-test results indicated that the high complexity task resulted in significantly higher syntactic complexity levels and greater fluency. However, results of the accuracy measure showed that the low-complexity group achieved a significantly higher mean score compared to the high-complexity group. Thus, this study lends partial support to both Robinson’s cognition hypothesis and Shehan’s trade-off hypothesis. The study also has pedagogical implications in designing and manipulating online materials for use with pedagogical tasks in the language classroom.